Media Literacy on Prevention of Pornography on Social Media and Sexual Violence on Factory Workers in Malaysia - Kholisoh, Nur Kholisoh; Ridaryanthi, Melly (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2024)
Social problems that are currently widespread are related to the impact of pornography on social media and the occurrence of sexual violence in society. Pornography has enormous dangers, especially if you are already addicted. Not only drugs are addictive, pornography can also cause addiction. In general, addiction to pornographic sites will have a negative impact on a person's character. Based on Bingham and Piotrowski's research in the Psychological Report entitled On-line Sexual Addiction, the characteristics of people who are addicted to cybersex are: lacking social skills, preferring to struggle with sexual fantasies, having fun communicating with the characters they create own imagination, and not being able to control myself from accessing pornographic sites and losing track of time. Apart from that, it can also result in sexual violence, such as: rape, sexual intimidation including threats or attempted rape, sexual exploitation, forced prostitution and sexual slavery. Sexual violence can happen to anyone, including men, women and children. This action, which can have a negative impact on the victims, can also occur anywhere, including among migrant factory workers abroad such as Malaysia. Therefore, it is necessary to carry out Media Literacy regarding Pornography on Social Media and Sexual Violence among Factory Workers in Malaysia as a form of preventing sexual violence and the impact of pornography on social media